(untitled) (Research, Society and Development, 2020)
The purpose of this article is to describe a health education action in the prevention of Diabetes Mellitus (DM) and Systemic Arterial Hypertension (SAH). This is a descriptive study, of the experience report type, lived by medical students from the Federal University of Pará, which carried out an action of health education in order to guide on the importance of physical exercises, food intake to 8th grade students at a municipal elementary and elementary school located in the area covered by Condor’s Family Health Strategy (ESF), located in the capital of Belém do Pará. An intervention was then proposed, which sought to analyze eating habits and knowledge about SAH and DM and also bring knowledge about healthy eating and the harms of an unruly diet. An incipient knowledge about SAH and DM is perceived, in addition to the consumption of industrialized foods, rich in fats, carbohydrates and sugars and a low adherence in the consumption of fruits and vegetables. However, it was evidenced that the practice of physical activities was predominant among students. Finally, it was noted that socioeconomic factors directly influence eating habits, the health-disease process of a population and that it is essential to implement public policies in the school environment aiming at healthy lifestyle habits for the prevention of prevalent chronic diseases.